2004
DOI: 10.2465/jmps.99.339
|View full text |Cite
|
Sign up to set email alerts
|

Crustal anatexis and evolution of granitoid magma in Permian intra-oceanic island arc, the Asago body of the Yakuno ophiolite, Southwest Japan

Abstract: A late Paleozoic crustal section of an intra oceanic island arc occurs in the Middle Unit (M Unit) of the Asago body from the Yakuno ophiolite, SW Japan. It consists of mafic metamorphic rocks and felsic to mafic later intrusions. The M Unit is composed of three lithologic zones: the Lower migmatite zone (L MZ), the Middle metagabbro zone (M MZ), and the Upper amphibolite zone (U AZ). The metamorphic grade of the lowest horizon of the M Unit reaches granulite facies conditions (P = 3.5 5.5 kbar at T = 850 860˚… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…1990; Herzig et al. 1997; Suda 2004). Thus, the Southern and Central zones have been considered as a collided arc‐back arc system (Hayasaka et al.…”
Section: Geological Outlinementioning
confidence: 99%
“…1990; Herzig et al. 1997; Suda 2004). Thus, the Southern and Central zones have been considered as a collided arc‐back arc system (Hayasaka et al.…”
Section: Geological Outlinementioning
confidence: 99%
“…Suda [8] and Suda and Hayasaka [7] suggested that the amphibolite and metagabbro in the Asago area possess geochemical affinities of BAB basalt (BABB), which are derived from a tholeiitic BABB source. These mafic rocks of BABB affinities are intruded by tonalite, quartz-diorite, and granodiorite of arc affinities.…”
Section: Yakuno Ophiolite and Associated Rocks In Asago Areamentioning
confidence: 99%
“…Suda [8] indicates that both the metagabbro and amphibolite exhibit various degrees of deformation and metamorphic textures, such as gneissosity with a preferred orientation of minerals. Foliation and lineation are strongly developed in the amphibolite suite in particular.…”
Section: Shrimp U-pb Zircon Datingmentioning
confidence: 99%
See 1 more Smart Citation
“…285 Ma Koide, 1986;Koide et al, 1987Ishiga, 1984 Yakuno rocks inset in Fig , 1997 Ishiwatari, 1985a;, 1996;Suda, 2004 , 1966;Shibata et al, 1977;1996;Ishiwatari et al 1991 1999 To-1…”
mentioning
confidence: 99%